Efficient heterogeneous catalytic system for chemoselective hydrogenation of unsaturated ketones in aqueous medium - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Polyhedron, 2010)
A highly chemoselective and green heterogeneous catalytic system of immobilized Ru(II)-phenanthroline complexes on amino functionalised MCM-41 material for the chemoselective hydrogenation of unsaturated ketones to unsaturated alcohols is demonstrated using water as a solvent The XRD and FTIR spectra show the highly ordered hexagonal nature of the MCM-41 even after encapsulation of the ruthenium complex The complex retains its configuration after anchoring as was confirmed by FTIR and UV-Vis analysis The detailed reaction parametric effect was studied for the hydrogenation of 3 methylpent-3-en-2-one to achieve complete conversion up to >99% chemoselectivity of 3-methylpent-3-en-2 ol The anchored heterogeneous catalysts were recycled effectively and reused five times with marginal changes in activity and selectivity The use of water as a solvent not only afforded high activity for the hydroge nation reaction compared to organic solvents but also afforded a green process Crown Copyright (C) 2010 Published by Elsevier Ltd All rights reserved
Keywords: 1 10 Phenanthroline; alpha beta Unsaturated ketone; Chemoselective hydrogenation; mesoporous materials; ruthenium

Heterogenized Ru(II) phenanthroline complex for chemoselective hydrogenation of diketones under biphasic aqueous medium - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Journal of Molecular Catalysis A-Chemical, 2010)
The chemoselective hydrogenation of acetylacetone to 4-hydroxypentan-2-one over immobilized ruthenium phenanthroline metal complexes in amino functionalized MCM-41 in biphasic aqueous reaction medium was investigated. The catalyst was characterized by XRD, TEM, surface analysis, FT-IR and UV-vis to understand the morphology, complex geometry, and XPS such that the oxidation state of the metal complex inside the MCM-41 framework could be understood. The use of water as a solvent, not only gives high activity and selectivity for hydrogenation of acetylacetone, but also gives a path for an environmentally safer process. The optimizations of ligand, metal to ligand ratio, the choice of solvent and other reaction parameters were studied in detail. The heterogeneous catalytic system gave a higher degree of chemoselectivity (99%) towards 4-hydroxypentan-2-one as compared to homogeneous catalyst when hydrogenation was carried out using water as a solvent. The immobilized ruthenium-phenanthroline complex was easily separated and reused. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 4-Hydroxypentan-2-one; acetylacetone; Chemoselective; Diketone; Hydrogenation; Phenanthroline; ruthenium; Water

Ru(II) phenanthroline complex as catalyst for chemoselective hydrogenation of nitro-aryls in a green process - Deshmukh, Amit A.; Prashar, Atul K.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Industrial & Engineering Chemistry Research, 2010)
Ru(II) Phenanthroline [Ru(II)(Phen)(n) where n = 1,2,3] complexes were used as highly chemoselective catalysts for hydrogenation of nitro aryls using molecular hydrogen in an aqueous media. Water, universal solvent, was used as a reaction mixture for hydrogenation of nitro-aryls to make the process green. The chemoselectivity in hydrogenation of substituted nitrobenzene to substituted aniline was obtained as high as >99% at about complete conversion of substituted nitrobenzene. The parametric effects, including effect of solvent, effect of ligand, effect of metal to ligand ratio, effect of temperature and pressure, were studied in detail to obtain the best results. The Ru(Phen)(n) was characterized by FTIR, UV-vis, and XPS.